Synthesis of Palm Oil Based Nano Carbon Using Nebulized Spray Pyrolysis - Nicolas Orlando; Windy Wilianti; Hans Kristianto; Arenst Andreas (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2017)
In this experiment, nano carbon material was synthesized with nebulized spray pyrolysis method using palm oil. The catalyst used in this study was ferrocene with a concentration of 0.015 g/ml; 0,020 g/ml; and 0.025 g/ml. The catalyst was contacted with carbon precursors using floating catalyst method. The carrier gas used in this study was nitrogen gas at a rate of 1.21 sccm. Nebulized process was conducted for 30 minutes with an operating temperature of 650°C; 700°C; 750°C; 800°C; 850°C; and 900°C. In this study, nano carbon material was synthesized by deposition directly on the walls of the tube / stainless steel reactor so no need a substrate as a growth medium carbon nano. The characteristics of nano carbon material was analyzed by several methods, such as SEM, EDS and XRD. The XRD analysis of carbon sample synthesized at 0.025 g/ml catalyst and all variations of temperature showed the presence of the C (002) and C (100) peak indicated a graphitic structures. From SEM observation, it can be seen that the structure of carbon nano spheres were found at temperature of 700°C and mixtures of nanotubes and nanospheres were established at temperature above 800°C.